Risk of hyperkalemia and combined use of spironolactone and long‐term ACE inhibitor/angiotensin receptor blocker therapy in heart failure using real‐life data: a population‐ and insurance‐based cohort†. (12th February 2015) - Abbas, Sascha; Ihle, Peter; Harder, Sebastian; Schubert, Ingrid
Abstract: Purpose: Clinical trials and few observational studies report increased hyperkalemia risks in heart failure patients receiving aldosterone blockers in addition to standard therapy. The aim of this study is to assess the hyperkalemia risk and combined use of spironolactone and long‐term ACE (angiotensin‐converting enzyme) inhibitor/angiotensin receptor blocker (ARB) therapy for heart failure in a real‐life setting of a heterogeneous population. Methods: Using claims data of the statutory health insurance fund AOK, covering 30% of the German population, we performed a nested case–control study in a cohort of heart failure patients receiving continuous ACE/ARB therapy ( n = 1, 491, 894). Hyperkalemia risk associated with concurrent use of spironolactone and ACE/ARB was calculated by conditional logistic regression in 1062 cases and 10, 620 risk‐set‐sampling‐matched controls. Results: Risk of hyperkalemia in heart failure patients was significantly associated with spironolactone use (odds ratio (OR) (95% confidence interval (CI)) = 13.59 (11.63–15.88) in all and 11.05 (8.67–14.08) in those with information on New York Heart Association (NYHA) stage of disease). In the NYHA subpopulation, higher risk estimates were observed in short‐term as compared with long‐term users (OR (95%CI) = 13.00 (9.82–17.21) and 9.12 (6.78–12.26), respectively). Moreover, the association was stronger in older (≥70 years of age) as compared with younger patients (<70 years of age) (OR (95%CI) = 12.32 (9.35–16.23) and 8.73 (5.05–15.08), respectively), although interaction was not significant ( p interaction = 0.07). Conclusions: Hyperkalemia risk associated with combined use of spironolactone and ACE/ARB is much stronger in real‐life practice than observed in clinical trials. Careful potassium level monitoring in concomitant users of spironolactone and ACE/ARB is necessary. Copyright © 2015 John Wiley & Sons, Ltd.